COVID-19 in the Americas: the role of collaborating centers in understanding lessons and best practices in pandemic preparedness and response - Francesca Nardi; Katherine Ginsbach; Kashish Aneja; Katie Gottschalk; Sam Halabi (Pan American Health Organization, 2023)
COVID-19 exposed major gaps in global, regional, state, and local responses to public health emergencies. In preparation for the WHA Special Session to consider the benefits of developing an international instrument on pandemic preparedness, the O'Neill Institute in partnership with Foundation for the National Institutes of Health convened 30 of the world's leading authorities on global health law, financing, biomedical science, implementation, and emergency response along with leaders from prominent international organizations. This meeting was followed by regional consultations convened in Latin America-Caribbean, Africa, and Southeast Asia. These high-level expert consultations generated in-depth discussions on weaknesses and persisting gaps in global pandemic preparedness and what a new international agreement might include to address them. Regional intergovernmental organizations like PAHO can work closely with related multilateral development banks to develop financial instruments that can smooth systemic economic disruption; and regional centers of research and manufacturing excellence can offer a strong front line for producing medicines and vaccines rapidly during a pandemic. With our research focused on the regional response to COVID-19 we are able to look at country responses individually and collectively to see how Latin America - Caribbean countries can capitalize and leverage their regional connections to strengthen their pandemic preparedness and response. By identifying existing gaps and examining the responses and approaches taken by PAHO, we can better understand the role of international and regional organizations and their collaborating centers in preparing and responding to pandemics.